Analisis Faktor Yang Berpengaruh Terhadap Return Saham (Studi Empiris Pada Perusahaan Manufaktur Sektor Farmasi Yang Terdaftar Di BEI) - Firdausi Nafiroh; Nurhidayah Nurhidayah; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine how the influence of market risk (X1), financial risk (X2), and business risk (X3) on stock returns (Y) in pharmaceutical manufacturing companies listed on the IDX. This research data was obtained from the financial statements of pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the website www.idx.co.id The research sample consisted of 9 pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange for 4 years, namely the 2017 period. -2020. The data analysis technique used is descriptive statistical analysis, and multiple linear regression analysis with the t test method. The results showed that the market risk variable had a significant positive effect on stock returns, financial risk had an insignificant negative effect on stock returns and the business risk variable had an insignificant negative effect on stock returns. With the magnitude of the determinant coefficient (R2) of 0.657 which indicates that 65.7% of the dependent variable stock returns can be explained by independent variables consisting of market risk, business risk, and financial risk and the remaining 55.7% is explained by other variables that are not researched. Keywords: Market Risk, Business Risk, Financial Risk, Return Saham